A review of the intersection between climate change, agriculture, health, and nutrition in Africa: costs and programmatic options - Mehra, Divya; Rael, Trula; Bloem, Martin W. (Frontiers in Sustainable Food Systems, 2024)
Climate change adversely affects Africa’s agriculture which would worsen the widespread food insecurity and nutritional deficiencies. Vulnerable populations, especially female farmers, women, and children are disproportionately affected. This paper synthesizes research on the intersections of climate change, food insecurity, agriculture, gender disparities, health and child nutrition, and micronutrient deficiencies in Africa. It explores the economic ramifications of these factors, particularly their impact on public health and economic stability and implications for productivity. The work aggregates insights into the current and future challenges of agricultural sustainability and the expected human capital development and economic costs of climate variations. The prevalence of hunger and undernourishment in Africa is notably higher compared to other regions. Climate change directly threatens agriculture, with anticipated reductions in crop yields, compounded by the negative impact of greenhouse emissions on the nutritional quality of staple foods. Female farmers contribute notably to agriculture, but their labor share is less dominant than previously assumed. High-temperature exposure, especially for outdoor workers and pregnant women, presents significant health risks, further affecting agricultural productivity and economic output. These interdependencies are presented in a framework along with suggested interventions that could be contextualized to address the climate drivers and interconnectivity across agriculture, health, and livelihoods. The interdependence between, food, agriculture, health, nutrition, and human productivity, all of which are exacerbated by the impacts of climate change in Africa, form a complex challenge with profound health and economic implications. A multifaceted strategy is needed, encompassing climate-resilient farming practices, gender-sensitive interventions, health-focused measures like micronutrient supplementation, and comprehensive economic policies. Such an approach is vital for sustainable development and improving health and well-being across the continent.